Multiphoton Intravital Calcium Imaging. Issue 1 (26th June 2018) - Cheetham, Claire E. J.
Abstract: Multiphoton intravital calcium imaging is a powerful technique that enables high‐resolution longitudinal monitoring of cellular and subcellular activity hundreds of microns deep in the living organism. This unit addresses the application of 2‐photon microscopy to imaging of genetically encoded calcium indicators (GECIs) in the mouse brain. The protocols in this unit enable real‐time intravital imaging of intracellular calcium concentration simultaneously in hundreds of neurons, or at the resolution of single synapses, as mice respond to sensory stimuli or perform behavioral tasks. Protocols are presented for implantation of a cranial imaging window to provide optical access to the brain and for 2‐photon image acquisition. Protocols for implantation of both open skull and thinned skull windows for single or multi‐session imaging are described. © 2018 by John Wiley & Sons, Inc.